On similarity of binary black hole gravitational-wave skymaps: to observe or to wait?. (30th November 2016) - Vitale, Salvatore; Essick, Reed; Katsavounidis, Erik; Klimenko, Sergey; Vedovato, Gabriele
Abstract: Localization estimates for GW150914, the first binary black hole detected by the LIGO instruments, were shared with partner facilities for electromagnetic follow-up. While the source was a compact binary coalescence (CBC), it was first identified by algorithms that search for unmodelled signals, which produced the skymaps that directed electromagnetic observations. Later on, CBC-specific algorithms produced refined versions, which showed significant differences. In this Letter, we show that those differences were not accidental and that CBC and unmodelled skymaps for binary black holes will frequently be different; we thus provide a way to determine whether to observe electromagnetically as promptly as possible (following a gravitational-wave detection), or to wait until CBC skymaps become available, should they not be available in low latency. We also show that, unsurprisingly, CBC algorithms can yield much smaller searched areas.